(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2003)
The effort to reintegrate into the social group those psychiatric patients who previously lived in big psychiatric institutions is of the most important milestones in the history of psychiatric care. New community-based psychiatric services offer higher levels of functioning and a better quality of life, but the implementation has proven more complex than some reformers originally hoped. Focusing on the ethos and some limitations of the new structures the present article deals with the words "asylum" and "institution" used by Greek psychiatric staff as synonymous although there is a fine differentiation between the two meanings. The terms "inside" or "outside" the community, which ostracize the "other side", the "inaccessible", and which rule out any possibility to converse with it and to reintegrate it, are also discussed. The subversive role of the "ambition to cure" is also underlined, as well as the necessity to leave room for the sacred and inaccessibly abandoning the effort to control and subjugate it. It could be suggested that rehabilitation projects should remain "open" to the "otherness" in order to be able to converse with it and to integrate it into the community as such, as it "is", i.e. as inaccessible and sacred, remaining open to the present and the oncoming, respecting the mystery of the "not any longer" and the "not yet", of the "where we are is where we are not". If God had looked into our minds he would not have been able to see there whom we were speaking of. L. Wittgenstein